Prebiotic composed of yeast (Saccharomyces cerevisiae) cell wall improves performance in broiler diets - Fornazier R.* (2024)
© (2024), (Sociedade Brasileira de Zootecnia). All rights reserved.This research aimed to evaluate the influence of a commercial prebiotic in different concentrations upon several parameters. To carry out the experiment, 640 male one-day-old broiler chicks were distributed in four treatments (0, 0.5, 1.0, and 1.5 kg/ton of yeast cell wall) with eight replicates of 20 birds per experimental unit, in randomized blocks. Prebiotic effects were assessed on performance, carcass yield and prime cuts, in addition to the litter quality (its content of nitrogen and phosphorus). There were significant improvements for weight gain and feed conversion ratio in experimental growth periods. However, prebiotic level at 1.0 kg/ton is enough to provide improvement in performance and similar yield parameters than the control group. Also, 1.5 kg/ton prebiotic inclusion in the diet promotes environmental benefits by reducing the phosphorus amount in the litter by 51%. Above 1.0 kg/ton prebiotic addition in broiler diets can be safely recommended, because it promotes both performance and environmental benefits.